An Interview with Michelle Metro-Roland: Tourism, Landscape, and the Signs / Entrevista com a Dra. Michelle Metro-Roland: Turismo, Paisagens e Signos - Kunz, Jaciel Gustavo (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2019)
ABSTRACT This interview was held in Kalamazoo, United States, in March 2019, by the PhD student in Geography, at the Federal University of RS, at the end of a five-month sandwich doctorate, with Dr. Michelle Metro-Roland as advisor. Metro-Roland has a classical background: her doctorate is in Geography, teaches Geography, and she is director of the Haenicke Institute for Global Education at the University of Western Michigan. Her research includes studies in Tourism and Landscape, based on Peirce's Semiotics. KEY-WORDS Tourism. Geography. Landscape. Semiotics. AUTORIA Michelle Metro-Roland – Professor and researcher, Western Michigan University, Kalamazoo, USA. Jaciel Gustavo Kunz - Master. Profesor, Fundação Universidade Rio Grande, Santa Vitória do Palmar, RS, Brazil. Currículum: http://lattes.cnpq.br/3082574114190162 E-mail: jacielkunz@gmail.com REFERENCES Knudsen, D. C., Metro-Roland, M. M. & Rickly, J. (2015). Tourism, aesthetics, and touristic judgment.Tourism Review International, 19(4), 179-195. Link Knudsen, D. C., Metro-Roland, M. M. Soper, A. & Geer (2008). Landscape, tourism, and meaning. Burlington and Aldershot: Ashgate Publishing. Metro-Roland, M. M. (2009). Interpretating meaning: an application of Peircean Semiotics to tourism. Tourism Geographies, 11(2), 270-279. Link Metro-Roland, M. M. (2011). Tourists, signs, and the city: semiotics of culture in an urban landscape. Abingdon: Routledge.